2022
DOI: 10.3390/cancers14174265
|View full text |Cite|
|
Sign up to set email alerts
|

Nucleolin Therapeutic Targeting Decreases Pancreatic Cancer Immunosuppression

Abstract: Background: The pancreatic ductal adenocarcinoma (PDAC) microenvironment is highly fibrotic and hypoxic, with poor immune cell infiltration. Recently, we showed that nucleolin (NCL) inhibition normalizes tumour vessels and impairs PDAC growth. Methods: Immunocompetent mouse models of PDAC were treated by the pseudopeptide N6L, which selectively inhibits NCL. Tumour-infiltrating immune cells and changes in the tumour microenvironment were analysed. Results: N6L reduced the proportion of regulatory T cells (Treg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…We sought to study the expression of TNFR2 by tumor infiltrated immune cells in orthotopic and immunocompetent mouse models of PDAC obtained by using mPDAC and Panc02 cell lines previously described [28]. We initially observed that mPDAC tumors have an immune-escape TME infiltrated by CD45 + immune cells, higly enriched in CD4 + Foxp3 + Tregs and characterized by low CD8 + T cell infiltration [29]. Here, tumor infiltrated lymphocytes (TILs) were isolated from mPDAC tumors and analyzed by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to study the expression of TNFR2 by tumor infiltrated immune cells in orthotopic and immunocompetent mouse models of PDAC obtained by using mPDAC and Panc02 cell lines previously described [28]. We initially observed that mPDAC tumors have an immune-escape TME infiltrated by CD45 + immune cells, higly enriched in CD4 + Foxp3 + Tregs and characterized by low CD8 + T cell infiltration [29]. Here, tumor infiltrated lymphocytes (TILs) were isolated from mPDAC tumors and analyzed by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Then, cell suspension was centrifuged in a gradient of Ficoll (GE Healthcare, ref: 17144003) for 40 min at 400g. All samples were stained as previously described [29] with the antibodies listed in Supplemental Material. Non-specific binding was blocked using anti-CD16/CD32 (Miltenyi, ref: 130-07-594).…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen differentially expressed proteins were identified, of which 10 were upregulated and four were downregulated (figure 7(i)). Among the set of common differentially expressed proteins, NUTF2, NCL, COTL1, RAB1B, PFN1, moesin, PGK1, GAPDH, PDIA4, tenascin C, complement C6, complement C8, and CFHR4 were associated with immune regulation [16][17][18][19][20][21][22][23][24][25][26][27]. Therefore, the significant changes in protein levels in 5% FS-TM were mainly concentrated in immune regulatory proteins compared with those of other media.…”
Section: Proteomics Analysis Suggested That Immune Regulation Mediate...mentioning
confidence: 95%
“…In the original publication [ 1 ], there was a mistake in Figure 3 A, Figure 6 E and Figure S1 A: there are white squares in the picture which cover the area that the authors want to indicate.…”
Section: Error In Figuresmentioning
confidence: 99%